Abundance of zooplankton from different zones (pelagic and littoral) and time periods (morning and night) in two Amazonian meandering lakes - Keppeler, Erlei Cassiano (Universidade Estadual de Maringa, 2003)
The abundance of zooplankton in two lakes of Southwest Amazonia was studied for 10 months in different regions and at different periods of the day. The lakes were Lago Amapá, located at 10°02′36″S, 67°50′24″W, and Lago Pirapora, at 9°27′21″S, 67°31′39″. Both lakes are characterized as oxbow lakes. The aim of this study was to compare the pelagic and littoral regions, as well as to determine differences in the distribution of zooplankton in the water column in the morning and at night. Collections were made by filtering water through a 55μm zooplankton net into a 5L Van Dorn bottle, collecting 4L from the top and 5L from the middle and bottom layers, totaling 14L of water for each sampling location. In addition, physical and chemical parameters were measured, including transparency, temperature, pH, dissolved oxygen, electrical conductivity and turbidity. Anova (analysis of variance) and Tukey's test were used. There was no statistically significant difference between the regions studied, nor between the two time periods examined. The results of the Pearson correlation (p<0.05) demonstrated that the physical and chemical characteristics of the water correlated with the cladocerans Moina spp. (represented by M. minuta and M. reticulata) and Ceriodaphnia cornuta, and that Daphnia gessneri was associated with Chaoboridae.
Keywords: Abandoned meander; Pelagic and littoral regions; Zooplankton; dissolved oxygen; river water; Brazil; littoral; nonhuman; pelagic zone; river; seasonal variation; water sampling; zooplankton; Ceriodaphnia cornuta; Chaoboridae; Daphnia gessneri; Moina; Moina minuta; Moina reticulata